Does Fiscal Decentralisation Strengthen Social Capital? Cross-Country Evidence and the Experiences of Brazil and Indonesia - de Mello, Luiz (OECD Economics Department Working Papers, 2010)
This paper tests the hypothesis that, by giving people more voice in the government decision-making process, fiscal decentralisation fosters social capital, measured in terms of interpersonal trust. Empirical evidence based on World Values Survey data and seemingly unrelated probit estimations for a cross-section of countries suggests that people living in federal/decentralised countries find it more important to have voice in government decisions than their counterparts living in unitary/centralised countries. Pro-voice attitudes are, in turn, associated with greater social capital. The cross-country estimations are complemented by country-specific regressions for Brazil and Indonesia on account of these countries. experiences with fiscal decentralisation. The results show that the cohorts of individuals that have been exposed to decentralisation are in general more pro-voice (and trustful of strangers in the case of Brazil) than their counterparts that have not been exposed to decentralisation. These findings are not driven by the effects of political liberalisation on people.s attitudes towards the importance of having voice in government decisions and interpersonal trust